PENINGKATAN LAYANAN PERPUSTAKAAN MELALUI INOVASI TEKNOLOGI DIGITAL DALAM MENCIPTAKAN RUANG PUBLIK BAGI SISWA - Yuspico Cornelis (ADISAM PUBLISHER, 2025)
School library management is the process of optimizing human, material, and budget contributions to achieve library goals. School libraries are still experiencing various obstacles, so they cannot run as they should. The obstacle comes from two aspects. The School Library consists of a collection of textbooks or readings that can support the learning process. The purpose of the library is to increase interest and reading habits. However, unlike libraries in general, school libraries have the main purpose of reading to learn or gain insight in the field of science. In the process of borrowing books at the library of SMP Negeri 15 Ambon, borrowers record borrowing data in a special notebook. The borrowing process that is now implemented poses several problems. Recording borrowing data by handwriting on a book is quite time- consuming, especially when there is a surge in the number of borrowers. In accordance with the obstacles experienced, the need for a technological innovation service to support the library management process. The implementation of the library application service of SMP Negeri 15 Ambon has succeeded in increasing efficiency in the process of borrowing and returning books. The integration also strengthens the system of book return control and automatic recording of late fines. The importance of digital services in libraries is a new breakthrough to improve performance efficiency in library management